ONLINE COMMUNITY AS A MEANS OF COMMUNITY EMPOWERMENT THROUGH LECTURER AND STUDENT SERVICE ACTIVITIES - Helleri Fivtrawati (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2022)
The high number of Covid-19 spreads in Indonesia has had an impact on all sectors. various things to break the chain of the spread of COVID-19 including physical distancing or physical distance restrictions from humans. This of course will limit and become an obstacle for the implementation of various activities that require direct face-to-face meetings, including community service. In this community service, this health education activity is carried out in the form of health with the theme of the activity